If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = 1 + -3x Reorder the terms: 7 + 2x = 1 + -3x Solving 7 + 2x = 1 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7 + 2x + 3x = 1 + -3x + 3x Combine like terms: 2x + 3x = 5x 7 + 5x = 1 + -3x + 3x Combine like terms: -3x + 3x = 0 7 + 5x = 1 + 0 7 + 5x = 1 Add '-7' to each side of the equation. 7 + -7 + 5x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 1 + -7 5x = 1 + -7 Combine like terms: 1 + -7 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2
| y+1=-1.375(x-11) | | (2x+1)+(x-4)=0 | | 2x-5+2=4-3+2 | | x-4=3(2-x) | | 5y+12=0 | | 8a-2=2a+4 | | x^2+x-77=0 | | 3x^2+19x=360 | | 5x+3=5(x+9) | | -5x+(-30)=15 | | 14x^3-10x^3= | | 2x+y+5y=180 | | 7x-3=7x-5 | | x^2+x=77 | | 4c=10+9c | | 0.3-0.7y=-0.2 | | 2x^3-50x^2=0 | | 8-4z=-5z | | 20=5(18x+14) | | 4x^2-1350=0 | | 12-6x=x-2 | | 8m-1=3m+44 | | 4y+9=9y-1 | | 4x+3-4x=x-7 | | 8v-1=4v-1 | | X^2*8x-20=0 | | 4x+3-4x= | | 2ab(3ab)= | | 4x+13=5x+5 | | 2.2x-12=-5.4 | | 38+-9283z=4+2z | | 4x(2)+9x-1=0 |